Federated GAN based biomedical image augmentation and classification for Alzheimer’s disease - Roy, Aditya; Rahman, Md. Mahbubur; Ahmed, Shafi (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.